Kiekybės turinio kilmininkas A. Baranausko ir K. Brugmanno užrašytuose tarmių tekstuose - Vasiliauskienė, Virginija (Baltistica, 2006)
THE PARTITIVE GENITIVE OF QUANTITY IN 19th CENTURY DIALECT TEXTS COLLECTED BY A. BARANAUSKAS AND K. BRUGMANN All the measure nouns found in the Eastern and Western High Lithuanian Kauniškiai dialect texts were divided into five subtypes. The abstract quantity nouns and the conventionalized measures usually govern the postposed partitive genitive. The placement of the partitive genitive may vary in the phrases with the nouns that have the meaning of containers and fractions (parts). The partitive genitives are usually postposed in complex phrases (tukstantis baczku smałos ‘(one) thousand barrels of pitch’; szventįto vandenio butelis ‘a bottle of sanctified water’). Words such as pusantro ‘one and a half’, pusė ‘a half’ are closely connected with numerals in their meaning and usage. The nouns lysė, ‘a bed’, dirva ‘ground (a field)’, lopinys ‘a piece’ can obtain the meaning of quantifiers when they describe different areas (sectors) of land. The postposition of the partitive genitive predominates (71-78 per cent) in these texts. The use of the preposed genitive in sequences with nouns denoting quantity makes up about a quarter of the occurrences, but in some of these the initial position is conditioned not by the quantity meaning, but rather by the meaning of purpose or definition. For Kauniškiai dialect texts the meaning of purpose in sentences with preposed genitives is in general not usual. That is, the position of the genitive in such sentences is not always connected with differences of meaning. The variation in the position of the genitive (especially in the Kauniškiai texts) is more closely connected with neutral or marked word order in the phrase. Therefore the use of preposed genitives is stipulated by three factors, namely, (a) the attributive meaning of the phrase (denoting purpose, definition, possession); (b) the marked word order in the phrase; (c) the alternation of the intonation in the sentence. Phrases with a postpositive genitive in the Kauniškiai texts can have a partitive meaning which is not significant. In these phrases the naming of the object expressed by the postpositive genitive as an entirety is more important. The content of quantity in the texts studied can be described as having three different possible sequences: (a) noun of quantity and postpositive genitive (maišas linų ‘bag of flax’); (b) noun of quantity and preposed genitive (linų maišas ‘bag of flax’ [literally *’of flax a bag’]); noun of quantity and a construction with su ‘with’ (maišas su linais ‘bag with flax’). The position of the attributive genitives and the genitives of quantity did not differ much as the word order in the attribute phrase of this period was not strictly defined.